Rescuing the Emergency – Multiple Expertise and IT in the Emergency Field - Dardelet, B.; Darcy, S. (Methods of Information in Medicine, 2003)
Objectives: The rapid growth, both in technical and social approaches to the innovation phenomenon in health care suggests that profound changes are occurring. The focus of the project was to evaluate these changes through the case study of the French emergency field.Methods: The consequences of information technology implementations in the Emergency Services are presented as models to investigate the importance of technical expertise, with both the involvement of all the stakeholders from the beginning of the design and the test of the new tool in real settings.Results and Conclusion: A new form of work resulted for the management of the crisis, which questioned the status of the actors and their actions, and the characteristics of the protocols of rescue. The outcome of this project was a new model built for the rescue of the emergency field which encompasses alternative forms of expertise.
Keywords: Emergency; telemedicine; collaborative work; information technology